Potensi Pengembangan Ekstrakurikuler Aquaponik dalam Upaya Menumbuhkembangkan Green Social Entrepreneur Pemula: Studi di SMP Negeri 1 Minggir, Sleman, DIY - Suprihanto, John; Dwi Putro, Sigit (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2023)
The purpose of this study was to develop and design an aquaponic extracurricular as an additional choice for students at Minggir 1 Public Middle School in accordance with the advantages of the school (local wisdom and content) and the environment. This research is included in qualitative research. The data needed in this study are primary data and secondary data. Qualitative descriptive analysis techniques, comparative (simple) descriptive analysis and formulative descriptive analysis as well as benchmarking were used in this study. It was explained that the Scout extracurricular is a mandatory extracurricular for all schools. As for non-obligatory extracurriculars, there are various extracurriculars. In the context of applied research and based on several considerations, a new productive extracurricular was chosen, namely aquaponics based on recycling ablution water at Minggir 1 Middle School. In the aquaponic cultivation process, a mental attitude is instilled to turn waste (threats) into blessings (opportunities). The process of mental evolution is carried out by junior high school students, in the family context, the weak are turned into strength. In this case, each (weak) student is able to become the strength of the family organization to improve family nutrition. Meanwhile, to ensure the implementation and continuity of new productive extracurriculars, the school issues a decree regarding the formation of institutions including human resources, organizational units, and their duties and functions. In the long term, the process of aquaponic cultivation is a process of continuous mental evolution (continuous quality improvement) to develop the mental attitude of novice green social entrepreneurs.